2015
DOI: 10.1186/s13028-015-0154-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondrosis, but not lameness, is more frequent among free-range pigs than confined herd-mates

Abstract: BackgroundOrganic pig production is expanding and amongst the objectives of organic farming are enhancing animal health and welfare. However, some studies have reported a higher prevalence of lameness and joint condemnation at slaughter in free-range/organic pigs than in conventionally raised pigs. Organic slaughter pigs have free-range housing in which indoor and outdoor access is compulsory, while in conventional farming the pigs are commonly confined to indoor pens. The present study evaluated the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
2
22
1
3
Order By: Relevance
“…When van Grevenhof et al [ 40 ] compared the joint health of pigs reared in different housing systems, a partially slatted concrete floor or a deep litter floor with extra space allowance, they found that the conventionally reared pigs were more affected by Osteochondrosis than the pigs reared in the deep litter floor. Similar results were found by Etterlin et al [ 41 ]. The authors concluded that the extra space allowed for the deep litter herd strengthened the joint supportive tissue and provided some pain relief through exercise.…”
Section: Healthsupporting
confidence: 92%
“…When van Grevenhof et al [ 40 ] compared the joint health of pigs reared in different housing systems, a partially slatted concrete floor or a deep litter floor with extra space allowance, they found that the conventionally reared pigs were more affected by Osteochondrosis than the pigs reared in the deep litter floor. Similar results were found by Etterlin et al [ 41 ]. The authors concluded that the extra space allowed for the deep litter herd strengthened the joint supportive tissue and provided some pain relief through exercise.…”
Section: Healthsupporting
confidence: 92%
“…Dairy cows commonly suffer from udder health disturbances and locomotion disorders; in 2013/2014, 26% of Swedish dairy cows were treated for some medical condition, although breeding in Sweden combines production, health, fertility and longevity traits into a 'total merit index' (Oltenacu and Broom 2010;Rodriguez-Martinez et al 2008). Joint lesions arise in all pig production systems, but they are more frequent and severe in organic compared with conventional production due to higher stress on pig joints in spacious and outdoor environments, as the leg conformation of modern, fast-growing pigs is not suited to the level of exercise required with large space allowances (Engelsen Etterlin et al 2015). Hence, it is worth discussing whether still higher yields per animal are desirable and in line with organic principles; attention should perhaps focus on improving animal health and welfare at current production levels or even accepting lower yield per animal if necessary.…”
Section: Animal Health and Welfarementioning
confidence: 99%
“…The total incidence of joint rejections at slaughter was very low in this study (1.3%). However, Etterlin et al (2015) have shown that the association between joint rejections at slaughter and gait scoring in pigs reared in organic production environments can be weak, and thus, joint rejection incidence at slaughter may be a poor indicator of clinical leg health. Thus, to assess pig welfare, it is important to investigate pig lameness during rearing rather than scanning the occurrence of osteochondrosis in carcasses.…”
Section: Discussionmentioning
confidence: 99%